2022
DOI: 10.12776/qip.v26i3.1753
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Product and Service Innovations of Different Level of Novelty in Knowledge Intensive SMEs: The Role of Open Innovation Patterns

Abstract: Purpose: The aim of the contribution is to evaluate the importance of domestic and foreign collaborative ties between knowledge-intensive SMEs and knowledge sources for the creation of product and service innovations which we differentiate according to the spatial level of novelty. Methodology/Approach: In order to test the validity of the hypotheses which were justified in the context of previous research we adopt an econometric approach and specifically, due to the nature of the dependent variable, the logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The findings of the present study are consistent with Hrivnák (2022), who found that product innovativeness (new and significantly improved products) influences performance. Specifically, it was found that 35% of small-scale enterprises introduced new products and services.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study are consistent with Hrivnák (2022), who found that product innovativeness (new and significantly improved products) influences performance. Specifically, it was found that 35% of small-scale enterprises introduced new products and services.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Hervas-Oliver et al (2021) have found limited use of external knowledge sources for process-oriented SMEs, whereas product-oriented SMEs develop internal capabilities through R&D and primarily access knowledge from the market. Spithoven et al (2013) discovered that SMEs seem to employ open innovation practices to a greater extent compared to larger firms, while Parida et al (2012) andHrivn ak (2022) found evidence that open innovation activities favor innovations with a higher degree of novelty. Gyamfi and Stejskal (2020) found that knowledge flows within members of corporate groups allows for the adoption of best practices and technologies, which in turn allows for more innovative outputs.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%